2015
DOI: 10.1021/acs.nanolett.5b04234
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Origin of Electrical Noise at Individual Grain Boundaries in Graphene

Abstract: Grain boundaries (GBs) are undesired in large area layered 2D materials as they degrade the device quality and their electronic performance. Here we show that the grain boundaries in graphene which induce additional scattering of carriers in the conduction channel also act as an additional and strong source of electrical noise especially at the room temperature. From graphene field effect transistors consisting of single GB, we find that the electrical noise across the graphene GBs can be nearly 10 000 times l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 55 publications
7
49
0
Order By: Relevance
“…Kochat et al also showed a strong correlation between the GB quality and its resistivity, where GBs with a wide region of disorder were more resistive than narrower GBs [27]. Meanwhile, the numerical simulations in figure 2 were made with perfectly connected polycrystalline samples, and thus yielded relatively low values of r GB [26].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 96%
See 2 more Smart Citations
“…Kochat et al also showed a strong correlation between the GB quality and its resistivity, where GBs with a wide region of disorder were more resistive than narrower GBs [27]. Meanwhile, the numerical simulations in figure 2 were made with perfectly connected polycrystalline samples, and thus yielded relatively low values of r GB [26].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 96%
“…When determining the GB resistivity, control of the Fermi level is also important, as four-terminal measurements have shown that the value of r GB can vary by one order of magnitude as a function of gate voltage, with the maximum occurring at the charge neutrality point (CNP) [20,27]. In figure 2, open circles represent measurements with the Fermi level at the CNP, closed circles are for measurements where the Fermi level is far from the CNP, and å's are for measurements where the Fermi level is unknown.…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the studies on graphene noise have been conducted on mechanically exfoliated single layer and bilayer devices [15,16,17,18,19]. It has been observed that the noise is usually smaller in bilayer structures compared to single layer devices.…”
Section: Introductionmentioning
confidence: 99%
“…The noise is dependent on the gate-induced carrier density and hence is expected to vary with the charge concentration at the surface [15]. Further, the noise magnitude has also been reported to depend on the disorder level, thickness of the grain boundaries [16] and also on the substrate on which it has been deposited [18,19]. Tan et al report that nanoribbons show lower flicker noise levels than planar graphene but the shot noise increases in graphene nanoribbons due to increased scattering in the presence of disordered edges [20,21,22].…”
Section: Introductionmentioning
confidence: 99%